Democratization of Health Services: Dynamics of Administrative Resistances (N'weti - comunicação para saúde, 2019)
This policy brief, apart from describing the dilemmas of the democratization process of health services it, aims to analyze its implications on the dynamics of social accountability in the health sector and, finally, to inform on possible ways for a more coherent democratization, considering the normative discourses
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; decentralization / descentralização; health / saúde

Sound of One Hand Clapping: Information Disclosure for Social and Political Action for Accountability in Extractive Governance in Mozambique - Awortwi, Nicholas; Nuvunga, Adriano (IDS, 2019)
Corruption through opaque public contracts costs Africa billions of dollars in revenue loss annually. Globally, initiatives to address this have centred on information disclosure (ID) but under what conditions does it work to promote accountability in the extractive sector that for a long time has seen its revenue management as being a major cause of conflict in Africa? Our study on this issue in Mozambique reveals intriguing findings, which suggest that protagonists of ID would need to recalibrate their strategies for promoting accountability. The study on ID in extractive governance in Mozambique has found 17 factors that connect to result in citizen and institutional inaction in demanding government accountability. The lessons from the study for policy and practice are that unless there is a link between ID and a government’s reputation, which scales up to the risk of a ruling government losing power, accountability is unlikely to occur when new information is disclosed.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; corruption / corrupção; decentralization / descentralização; extractive industries / indústrias extractivas; natural resources / recursos naturais

Relatório De Diagnóstico Sobre Transparência, Governação E Corrupção - República de Moçambique (International Monetary Fund (IMF), 2019)
A economia de Moçambique encontra-se num ponto de viragem, e os esforços para abordar as vulnerabilidades em matéria de governação e corrupção podem ter um impacto positivo duradouro. Já tomámos medidas para abordar as vulnerabilidades em matéria de governação e corrupção. Contudo, reconhecemos que subsistem falhas em diversas áreas relevantes da economia. A fim de abordar algumas das debilidades restantes, temos reformas de governação em curso e em perspectiva em várias áreas, muitas delas apoiadas por diversos doadores. Reconhecemos que a implementação eficaz continua a suscitar preocupações. Reconhecemos que a falta de transparência pode igualmente exacerbar as preocupações com a governação e agravar o risco de conflitos de interesse. Embora reconheçamos que temos um papel essencial a cumprir na melhoria da governação e no combate à corrupção, não podemos fazê-lo sozinhos. Estamos preparados e dispostos a tomar medidas concretas.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; corruption / corrupção; transparency / transparência

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde